Implementation of the Internet of Things for Real-Time Monitoring and Control of Environmental Conditions - Indra Sari Kusuma Wardhana; Almurozy Mursidan (Technema: Journal of Intelligent Engineering and Computing, 2026)
The development of the Internet of Things (IoT) enables environmental conditions to be monitored and controlled in real time through the integration of sensors, microcontrollers, wireless communication, monitoring interfaces, and actuators. This study aims to implement an IoT-based system for real-time environmental monitoring and automatic control based on measured environmental conditions, particularly temperature and humidity. The developed system integrates DHT11, MQ-2, and MQ-6 sensors with Arduino Uno R3, NodeMCU ESP8266, wireless communication, a monitoring dashboard, and relay-controlled actuators. Sensor measurements are processed and transmitted to the monitoring system, while predefined temperature thresholds are used to determine actuator activation. Experimental evaluation was conducted through sensor accuracy, communication reliability, monitoring, and automatic control tests. The results showed average temperature and humidity measurement errors of 0.78% and 1.46%, respectively, indicating relatively small deviations from reference measurements under the tested conditions. Communication testing achieved a 100% success rate for 100 transmitted packets with no packet loss, while the average communication delay was 412 ms. Automatic control testing achieved 100% success across 10 trials using a 30 °C temperature threshold. These findings demonstrate that the integrated IoT architecture can support responsive environmental monitoring and automated control within the tested operating conditions.